KEDUDUKAN ANAK LUAR KAWIN DALAM PEMBAGIAN WARIS (ALM) JUNIKO MENURUT HUKUM WARIS PERDATA BARAT (STUDI PUTUSAN NOMOR 302/PDT.G/2020/PN.JKT.PST): The Status Of Children Off The Wed Regarding The Division Of Juniko's Inheritance According To Western Civil Inheritance Law (Study Of Decision Nober 302/Pdt.G/2020/Jkt.Pst) - Septiani, Dilla Dwi; Bakri, Khairani (Faculty of Law, Universitas Trisakti, 2024)
The position of extra-marital children on the inheritance of parents who recognize them is essentially equivalent to legal children based on Article 280 of the Civil Code. The process of recognizing extra-marital children can be divided into 2 (two) groups: First, Voluntary Recognition and Forced Recognition. How is the position of extra-marital children in the distribution of inheritance based on Western Civil Inheritance Law? 2. Will the contents of the verdict of the judge of the Central Jakarta District Court Number 302/Pdt.G/2020/Jkt.Pst, parts Number 1 and 5 regarding the distribution of the estate of (alm) Juniko to the heirs be in line or not by Western Civil Inheritance Law? This research is normative research and descriptive research. The data utilized is secondary data through a literature study. Data management is carried out qualitatively. Concluding is done in a deductive way. Conclusion: the position of extra-marital children in the distribution of inheritance according to Western Civil Inheritance Law will later obtain inheritance if there is recognition as contained in Article 280 of the Civil Code. The Central Jakarta District Court Decision Number 302/Pdt.G/2020/Jkt.Pst is not by Western Civil Inheritance Law.